Effects of nitrogen and precipitation on the life history of spring- and autumn-germinated plants of Hypecoum erectum L. (Papaveraceae) - Shanlin Yang; Rongrong Cui; Xueying Yang; Kexin Sun; Yuwei Liu; Bing Han; Chunzhi Zhou; Bingyan Liu (PLoS ONE, 2025)
Nitrogen deposition and precipitation are the topics of current global climate change, and also the major environmental factors influencing plant growth. This study utilized the ephemeral plant H. erectum, which is distributed in the Gurbantunggut Desert in northwest China, as the experimental material to analyze the influence of nitrogen deposition and water-nitrogen interaction treatment on the phenology, survival rate, plant traits, biomass accumulation, and seed dormancy of spring- and autumn-germinated plants. The research results indicate that increased nitrogen increases the survival rate of H. erectum spring- and autumn-germinated plants. There is no significant impact on phenological events. However, plant traits such as leaf number, leaf area, branch number, seed quantity, and biomass accumulation are all reduced. During the growth and development process, more biomass is allocated to reproductive organs, and result in the production of a large number of non-dormant seeds. Therefore, in arid and semi-arid ecosystems, nitrogen deposition plays a crucial role in the survival of plants and the rapid reproduction of offspring. After water-nitrogen interaction treatment, the survival rate of H. erectum spring- and autumn-germinated plants significantly increased. The main phenology (leafing date, first flowering date, last flowering date, fruiting date and withering date) were delayed, extending the life cycle of reproductive growth. Biomass accumulation in all organs increased with a same allocation trend, produce a large number of dormant seeds. Therefore, precipitation not only influences the biomass allocation of plants and regulates their nitrogen uptake, changes the growth mechanisms of plants in adverse environments.